A GR/Impedance probe proves unsuitable for measuring GR depth in Australian lamb carcases. (July 2017) - Fowler, Stephanie M.; Hoban, Jordan M.; van de Ven, Remy; Boyce, Mal; Williams, Andrew; Pethick, David W.; Hopkins, David L.
Abstract: Multiple studies were conducted at 3 abattoirs to determine the potential of a dual function GR/Impedance probe to measure GR soft- tissue depth (depth at the 12th rib, 110 mm from the mid line of the carcase) of typical lamb carcases processed in Australia. Lamb carcases (1016) were measured approximately 25 min post slaughter with the probe and a GR knife as the most commonly used measurement. Modelling indicated that variation in the measurement using the probe compared to the measurement using the knife occurred with increasing carcase weight and fatness as well as between different abattoirs. Consequently, the probe in its current design cannot provide the repeatable measurement required by industry. Highlights: A GR/Impedance probe was shown to be unsuitable to measure GR tissue depth in lambs Variation in GR tissue depth measures were associated with the weight of carcases. Increasing fatness also reduced the ability to measure GR tissue depth with the probe.